Basic Serological Testing - Alhabbab, Rowa Yousef (Techniques in Life Science and Biomedicine for the Non-Expert,, 2018)
This book discusses in detail various serological tests that are used to identify medical conditions and diseases, from a general overview of each test to the equipment and steps needed to carry them out. The book is aimed specifically at immunology students and professionals who may occasionally need to use these tests, and thus lack training and experience in performing them. The book provides a brief overview of the immune system, including antibodies, antigens, and their interactions. The bulk of the book is comprised of 16 chapters that each explain different serological tests. These chapters start with a general introduction of the test or disease being detected, followed by the test principle, reagents required for the test, procedures and steps to perform the test, and, finally, result interpretation. Both test principles and result interpretation segments include illustrations to aid comprehension. In addition, the book also enables the reader to distinguish between positive and negative results in serological testing.